Implicit type Volterra integrodifferential equation - Pachpatte, B. G. (Tamkang Journal of Mathematics, 2010)
In this paper we study the existence, uniqueness and other properties of solutions of a certain nonlinear implicit type Volterra integrodifferential equation. The Banach fixed point theorem and a certain integral inequality with explicit estimate are used to establish the results.